1997
DOI: 10.1097/00000658-199709000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Enteral Feeding Results in Impaired Respiratory Mechanics and Decreased Mobility

Abstract: ObjectiveThe authors set out to determine whether immediate enteral feeding minimizes early postoperative decreases in handgrip and respiratory muscle strength. Summary Background DataMuscle strength decreases considerably after major surgical procedures. Enteral feeding has been shown to restore strength rapidly in other clinical settings. MethodsA randomized, controlled, nonblinded clinical trial was conducted in patients undergoing esophagectomy or pancreatoduodenectomy who received immediate postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(117 citation statements)
references
References 42 publications
6
105
1
5
Order By: Relevance
“…Previous reports also showed that severe jejunostomy-related complications requiring reoperation occur in 0-3% of all patients, which was confirmed by the present study (9,11,12,16,18,20,23). Furthermore in a randomized trial it was shown that immediate jejunostomy tube feeding may impair respiratory mechanics and may decrease mobility following esophagectomy (24).…”
Section: Discussionsupporting
confidence: 89%
“…Previous reports also showed that severe jejunostomy-related complications requiring reoperation occur in 0-3% of all patients, which was confirmed by the present study (9,11,12,16,18,20,23). Furthermore in a randomized trial it was shown that immediate jejunostomy tube feeding may impair respiratory mechanics and may decrease mobility following esophagectomy (24).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, most clinical studies did not compare enteral nutrition and total parenteral nutrition in a randomized fashion [14,22,24]. Of the studies performed in a prospective randomized fashion [9,25,26], the patients studied were not limited to esophageal cancer patients, such that the bona fide effects of EEN in esophageal surgery were not clear. Furthermore, the term Bearly^was defined as EN started within 24-48 h after admission or surgery [27]; however, EN started within 24 h had shown no advantage for the postoperative course in esophageal cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, postoperative enteral nutrition (EN) and/or parenteral nutrition (PN) have become routine management in such cases, and recent studies demonstrated that EN initiated within 24-48 h after esophagectomy reduced the length of hospital stay [5,6], postoperative morbidity, and the rate of life-threatening complications [7]. However, because some studies have not shown any clinical benefits with postoperative early enteral nutrition (EEN) after esophagectomy over PN [8,9] and indicated the importance of PN after esophagectomy as a nutrition therapy [10], so the superiority of EEN after esophagectomy has remained controversial. The aim of the present retrospective study was to clarify the superiority of EEN for postoperative course compared with PN in patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients undergoing esophagectomy or pancreaticoduodenectomy did not receive enteral nutrition during the 6 days postoperatively, there were no significant differences in grip strength, respiratory muscle strength, or recovery of walking ability, compared with nutritionally fed patients after jejunostomy [142]. In the EPaNIC study, 4640 patients were randomized to early parenteral replacement therapy (early PN group) or tolerating caloric deficiency for first week in ICU (late PN group) [143].…”
Section: Nutritional Strategiesmentioning
confidence: 99%